2014
DOI: 10.1371/journal.pone.0094849
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of Inshore Marine Mammals in Eastern Australia Is Predicted by Freshwater Discharge and Air Temperature

Abstract: Understanding environmental and climatic drivers of natural mortality of marine mammals is critical for managing populations effectively and for predicting responses to climate change. Here we use a 17-year dataset to demonstrate a clear relationship between environmental forcing and natural mortality of inshore marine mammals across a subtropical-tropical coastline spanning a latitudinal gradient of 13° (>2000 km of coastline). Peak mortality of inshore dolphins and dugongs followed sustained periods of eleva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 49 publications
1
54
0
Order By: Relevance
“…Time series analysis ( Figures 2 and 4) showed that turtle stranding is cyclical across years with more turtles stranding during the months coming out of winter (August to November) and fewer turtles stranding in the months when waters start to cool (April to June). Further periods of unusual extreme weather may result in outliers in these normal seasonal patterns [8][9][10]27]. These outliers warrant independent investigation as they relate to periods of increased need for resources and rehabilitation if turtle deaths are to be minimized by intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Time series analysis ( Figures 2 and 4) showed that turtle stranding is cyclical across years with more turtles stranding during the months coming out of winter (August to November) and fewer turtles stranding in the months when waters start to cool (April to June). Further periods of unusual extreme weather may result in outliers in these normal seasonal patterns [8][9][10]27]. These outliers warrant independent investigation as they relate to periods of increased need for resources and rehabilitation if turtle deaths are to be minimized by intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Stranded cetaceans are recorded in the StrandNet database for the state of Queensland (Meager and Limpus, 2014). For the purposes of the current study, we use the term 'strandings' for cetaceans that were reported to be in ill health, injured, incapacitated or dead, whether beach cast or observed at sea.…”
Section: The Queensland Marine Wildlife Strandings and Mortality Progmentioning
confidence: 99%
“…However, the relationship between strandings records and population trends in live assemblages can be confounded by a range of factors such as unusual stranding events (e.g. epizootics or mass strandings), environmental variation (Meager and Limpus, 2014), carcass drift (Peltier et al, 2012) or reporting effort. It is also arguable whether strandings records represent the demographics of living communities, because the risks of mortality or morbidity characteristically vary with ontogeny (Perrin et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…They also stated that elevated rates of turtle mortalities have occurred following similar weather events in the past (Meager and Limpus, 2012a). Meager and Limpus (2014), found links between periods of elevated freshwater discharge, low air temperatures and increased dugong mortality. They found that 9 months after elevated freshwater discharge there was an increase in dugong mortality.…”
Section: Extreme Weather and Marine Turtlesmentioning
confidence: 98%
“…It is known that within a year (short-term) of these types of catastrophes, marine megafauna show an increase in the number of stranding, mortalities and exacerbated by poor-health conditions (Meager and Limpus, 2014). However, the long-term (one or more years) and cumulative effect of all of these events on marine turtles is unknown.…”
Section: Chapter 1 Review Of Literaturementioning
confidence: 99%